2022
DOI: 10.21203/rs.3.rs-2019287/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asymptomatic Plasmodium falciparum carriage and clinical disease: a five-year community-based longitudinal study in The Gambia.

Abstract: Background Carriers of persistent asymptomatic Plasmodium falciparum infections constitute an infectious reservoir that maintains malaria transmission. Understanding the extent of carriage and characteristics of carriers specific to endemic areas could guide use of interventions to reduce infectious reservoir. Methods In eastern Gambia, an all-age cohort from four villages was followed up from 2012 to 2016. Each year, cross-sectional surveys were conducted at the start and end of the malaria transmission sea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Consistent with previous studies in The Gambia [6,13,20], the prevalence of infection was lower in children under 5 years of age than in older children and adults, possibly due to the seasonal malaria chemoprophylaxis programme (monthly antimalarial treatment during the transmission season) [28,29]. The higher prevalence of infection and high parasite densities in older children than in adults may be the result of acquired immunity that makes adults better protected and able to better control parasite growth when infected [30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous studies in The Gambia [6,13,20], the prevalence of infection was lower in children under 5 years of age than in older children and adults, possibly due to the seasonal malaria chemoprophylaxis programme (monthly antimalarial treatment during the transmission season) [28,29]. The higher prevalence of infection and high parasite densities in older children than in adults may be the result of acquired immunity that makes adults better protected and able to better control parasite growth when infected [30].…”
Section: Discussionsupporting
confidence: 93%
“…The discrepancy between asymptomatic infections being a protection or a risk for reinfection/clinical malaria could be explained by the large range of malaria transmission intensity between the cited studies, as well as local environmental conditions. For example, a recent study conducted in The Gambia revealed that in the semi-urban villages dry season carriage was associated with an increased risk of clinical malaria during the following transmission season, whereas such risk was lower in rural villages [6]. Finally, a pooled analysis also demonstrated the importance of transmission intensity with risks of subsequent clinical malaria, as well as host age and polyclonality of infection [19] although this meta-analysis encompassed studies that evaluated clinical infections within the same asymptomatic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria In The Gambia remains endemic, with almost all cases being caused by P. falciparum, although the incidence is lower than experienced two decades ago [16][17][18][19]. To analyse intrinsic multiplication rates of parasites, isolates from cryopreserved blood samples of hospital cases and community infections have been newly established and assayed in under exponential growth conditions in culture.…”
Section: Introductionmentioning
confidence: 99%
“…Asymptomatic individuals serve as reservoirs of infections and contribute to the persistence of transmission impending malaria reduction and elimination efforts [27]. The scarcity of data on the scope and prevalence of asymptomatic malaria presents a critical gap in malaria control efforts.…”
Section: Introductionmentioning
confidence: 99%